2023
DOI: 10.1037/xge0001272
|View full text |Cite
|
Sign up to set email alerts
|

Intent matters: Resolving the intentional versus incidental learning paradox in episodic long-term memory.

Abstract: Decades of research have established that the intent to remember information has no effect on episodic long-term memory. This claim, which is routinely taught in introductory cognitive psychology courses, is based entirely on pure-list between-subjects designs in which memory performance is equal for intentional and incidental learning groups. In the current 11 experiments, participants made semantic judgements about each word in a list but they had to remember only words presented in a specific color. We demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
41
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(52 citation statements)
references
References 71 publications
6
41
1
Order By: Relevance
“…As pointed out by Popov and Dames (2022), many previously published experiments have shown that when words are processed by an incidental semantic processing task, subsequent recall levels are not increased by the addition of intentional learning instructions (Hyde & Jenkins, 1969, Experiments 1, 2, and 3; Hyde & Jenkins, 1973; Johnston & Jenkins, 1971; Oberauer & Greve, 2022, Experiments 1, 2, and 3; Postman & Adams, 1956), or in comparison with a group whose task is simply to learn the list (Hyde, 1973; Till et al, 1975). In the same vein, Evans and Baddeley (2018) compared groups of participants who either performed an orienting task on each of a series of scenes, or were additionally instructed to learn the scenes for a later memory test.…”
Section: Endorsing the Conclusion Of Craik And Tulving (1975)mentioning
confidence: 96%
See 2 more Smart Citations
“…As pointed out by Popov and Dames (2022), many previously published experiments have shown that when words are processed by an incidental semantic processing task, subsequent recall levels are not increased by the addition of intentional learning instructions (Hyde & Jenkins, 1969, Experiments 1, 2, and 3; Hyde & Jenkins, 1973; Johnston & Jenkins, 1971; Oberauer & Greve, 2022, Experiments 1, 2, and 3; Postman & Adams, 1956), or in comparison with a group whose task is simply to learn the list (Hyde, 1973; Till et al, 1975). In the same vein, Evans and Baddeley (2018) compared groups of participants who either performed an orienting task on each of a series of scenes, or were additionally instructed to learn the scenes for a later memory test.…”
Section: Endorsing the Conclusion Of Craik And Tulving (1975)mentioning
confidence: 96%
“…
This commentary is a reply to the article "Intent matters: Resolving the intentional versus incidental learning paradox in episodic long-term memory" by Popov and Dames (2022). In their article, the authors question the view that once adequate deep, elaborate, and organizational processes have been induced incidentally, the intention to learn adds nothing further to the level of subsequent retention.
…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…According to the specific impact account (Figure 2), representations integrated in an event-file could be selectively up-or downregulated without affecting the associative weights that bind stimulus features to response features in the same event-file. If so, this finding has profound implications for the recently raised question which processes allow for the top-down 2 Note, that a recent study could also show that the intention to remember strengthens itemcontext bindings (as compared to a process-only condition) even when using a deep semantic processing task similar to the one used in the present study (Popov & Dames, 2022; please note that there was however no forget instruction).…”
Section: Discussionmentioning
confidence: 51%
“…Adding to this initial research, a recent study demonstrated that the intention to remember creates stronger memory for the bindings between stimuli and their context even when using a deep semantic processing task (as compared to a process-only condition; Popov & Dames, 2022; please note that there was however no forget instruction). Therefore, for verbal material, there is some evidence that at least the intention to remember strengthens declarative bindings.…”
Section: No Directed Forgetting Of Stimulus-response Associationsmentioning
confidence: 98%